A Test Process Model to Evaluate Performance Impact of Privacy Protection Solutions - Mello, Victor; Basso, Tania; Moraes, Regina (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2014: Anais do XV Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2014.22946, 2014)
Organizational Information Systems (IS) collect, store, and manage personal information through web applications and services. Due to regulation laws and to protect the privacy of clients, such information must be kept private. Some solutions were developed to protect privacy personal information. Obviously, this additional resource will produce a performance impact and evaluating it is essential to determine the feasibility of the solution. This paper presents a process model to evaluate the performance impact introduced by privacy protection solutions in web applications. Case study shows the tests were useful to identify the conditions in which the solution under evaluation is able to work with minimal performance impact.